TRANSMISSION DEVICE ASYNCHRONOUS - CYCLIC TELEMASURING SYSTEM - Khalilov Orzikul; Pardabayev Abdurakhim (Galaxy International Interdisciplinary Research Journal, 2021)
Asaresultofthis final qualification work, the transmitting device of the asynchronous-cyclic system was analyzed. General information on asynchronous cyclic telemetry systems was presented. The main blocks of the device are investigated. The selected element base has been described. A metrological analysis was also performed[1].